Formulasi Sediaan Pomade Ekstrak Daun Meniran (Phyllanthus niruri L.) Sebagai Perangsang Penumbuh Rambut Pada Kelinci - Syafitri, Anggun; Marbun, Viktor Edyward; Laia, Sardamai (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Background: Meniran petroleum ether extract 2% which contains lignans and terpenoids can increase hair growth activity by inhibiting 5α-reductase. In addition, the ethanol extract of candlenut seeds from the same family as meniran Flavonoids and phenols can also stimulate hair growth. Previous studies have also shown that quercetin also has activity to increase hair growth. Meniran is also known to contain the flavonoids quercetin, nirurin, rutin, quercitrin, astragalin and galocatechin. So meniran ethanol extract was chosen for this study. Based on a literature search about this research, the researcher was interested in formulating meniran leaf extract pomade (Phyllanthus niruri L.) as a hair stimulant in rabbits (Oryclolagus cunucilus). Purpose: To determine the formulation of meniran leaf extract pmade (Phyllanthus niruri L.) which is good in stimulating hair growth in rabbits. Methods: The method used was an experimental study to test the characteristics of pomade preparations with meniran leaf extract concentrations of 5%, 7.5% and 10% with organoleptic, homogeneity, spreadability, pH, irritation and freeze-thaw parameters. Results: From the results of the research on the characteristic test of pomade preparations on formulations of formula I, formula II and formula III it was found that they fulfilled the characteristics of pomade while F0 did not meet the spreadability requirements. Conclusion: Among the three formulations, it was found that pomade with formula III had the effectiveness of a good hair growth stimulant and could compete with the positive control.